Coping, taming or solving: alternative approaches to the governance of wicked problems. (2nd November 2017) - Daviter, Falk
ABSTRACT: One of the truisms of policy analysis is that policy problems are rarely solved. As an ever-increasing number of policy issues are identified as an inherently ill-structured and intractable type of wicked problem, the question of what policy analysis sets out to accomplish has emerged as more central than ever. If solving wicked problems is beyond reach, research on wicked problems needs to provide a clearer understanding of the alternatives. The article identifies and explicates three distinguishable strategies of problem governance: coping, taming and solving. It shows that their intellectual premises and practical implications clearly contrast in core respects. The article argues that none of the identified strategies of problem governance is invariably more suitable for dealing with wicked problems. Rather than advocate for some universally applicable approach to the governance of wicked problems, the article asks under what conditions different ways of governing wicked problems are analytically reasonable and normatively justified. It concludes that a more systematic assessment of alternative approaches of problem governance requires a reorientation of the debate away from the conception of wicked problems as a singular type toward the more focused analysis of different dimensions of problem wickedness.